Rethinking Japanese security internal and external dimensions - Katzenstein, Peter J. (Security and governance series., 2008)
Contains essays which focus on Japan's championing of "comprehensive security". This book focuses on counter-terrorism and national security. It is suitable for students and scholars of Japanese politics, security studies and international relations.